Od polskich słów do polskich zdań. W poszukiwaniu słów kluczy do polskiej kultury - Niewiara, Aleksandra (Forum Lingwistyczne, 2014)
<!--EndFr--> From the Polish words to the Polish phrases The quest for the key words to the Polish culture The paper summarizes the ethno-linguistic research on the Polish words (understood as the names of Polish values, both positive and negative), and the Polish phrases (idioms and quotations seen as elements of Polish collective memory which are supposed to be explanatory instruments in the process of description of the Polish culture or, for instance, in creation of the self-portrait of a Pole). The main part of the paper is a presentation of the author’s research inspired by Anna Wierzbicka’s theory of the key words to the cultures and discussion on rules and methods of recognizing the key words and arranging them in a culturally motivated hierarchy. The author perceives the key words – in accordance with the principles of the cognitive semantics – as a linguistic expressions which constitute access sites to an entire network of culturally profiled notions. She claims that the important part of the network of Polish notions is, in the term of cognitive semantics, “profiled” and in other words “programmed” by democratic ideas of the old Polish society: the Polish noblemen (szlachta). By means of the analysis of a few texts, the author proves that there is a connection between the notions of democratic rights of liberty (wolność) and equality (równość) and terms and notions repeatedly used in Polish self-description: willfulness (swawola), anarchy (anarchia), rebelions (bunty), envy (zazdrość, zawiść). Another link is found between the democratic institution of Polish sejm/sejmik (parliament) which is well established in culture and in language and characterized by speeches delivered from different points of view, and the notions of Polish quarrels (kłótnie), strifes (swary) and disputes (spory). Key words: key words to cultures, democratic ideas in Polish culture, network of cultural concepts